FAKTOR-FAKTOR PENYEBAB BELUM TERBENTUKNYA SERIKAT PEKERJA UNIT KERJA PERUSAHAAN DI KABUPATEN SLEMAN - Ari Hernawan (Fakultas Hukum Universitas Gadjah Mada, 2008)
This research shows that several factors have caused the unavailability of worker union. The factors include the government, the companies, the laws and the workers. The government does not actively socialize and supervise worker unions. Moreover, employers prefer an unofficial worker union rather than the official one. The Indonesian Industrial Relationship Law and Worker Union Law regard worker union as a right rather than an obligation. However, the workers do not fully aware of the benefit of the union. Rather, the workers consider the requirement of providing article of association and financial autonomy as burdens in establishing the union. The condition is getting worse with the fact that the workers do not have opportunity to establish the worker union.